Numerical solution of Volterra integral equations with weakly singular kernels which may have a boundary singularity - Kolk, Marek; Pedas, Arvet (Mathematical Modelling and Analysis, 2009)
We propose a piecewise polynomial collocation method for solving linear Volterra integral equations of the second kind with kernels which, in addition to a weak diagonal singularity, may have a weak boundary singularity. Global convergence estimates are derived and a collection of numerical results is given. First published online: 14 Oct 2010